Current Therapeutic Options for Heart Failure in Elderly Patients. (15th November 2017) - Guerra, F.; Brambatti, M.; Matassini, M. V.; Capucci, A.
Abstract : Heart failure (HF) is a major and growing public health problem with high morbidity and mortality (Ponikowski et al., 2016). It affects 1-2% of the general population in developed countries, and the average age at diagnosis is 76 years. Because of a better management of acute phase and comorbidities, HF incidence is increasing in elderly patients, with a prevalence rising to 10% among people aged 65 years or older (Mozaffarian et al., 2014). Therefore, a substantial number of elderly patients need to be treated. However, because of clinical trial exclusion criteria or coexisting comorbidities, currently recommended therapies are widely based on younger population with a much lower mean age. In this review, we will focus on available pharmacological, electrical, and mechanical therapies, underlining pros, cons, and practical considerations of their use in this specific patient population.